2012
DOI: 10.1259/bjr/19566194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of virtual unenhanced CT obtained from dual-energy CT urography for detecting urinary stones

Abstract: Objective: The aim of our study was to determine if virtual unenhanced CT (VUCT) is equivalent to unenhanced CT (UCT) for detecting urinary stones. Methods: Our institutional review board approved this retrospective study, which was compliant with the Health Insurance Portability and Accountability Act. A total of 80 stones were detected in 32 patients among 146 consecutive patients undergoing dualenergy CT urography. The number and size of stones were recorded on nephrographic VUCT (NVUCT) and excretory VUCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…12 To date, many studies of the clinical application of VNC images have been performed, mainly in the abdomen for characterizing renal masses, 13 applications in pancreatic CT, 14 and detecting urinary or biliary stones. 15,16 Most of those studies proved that VNC images were useful and feasible, though the imaging quality was inferior to that in the TNC images. Very few studies were performed on the detection of intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…12 To date, many studies of the clinical application of VNC images have been performed, mainly in the abdomen for characterizing renal masses, 13 applications in pancreatic CT, 14 and detecting urinary or biliary stones. 15,16 Most of those studies proved that VNC images were useful and feasible, though the imaging quality was inferior to that in the TNC images. Very few studies were performed on the detection of intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al (26) reported that the anatomic structures viewed on unenhanced CT images may be poorly depicted on virtual unenhanced CT images, and stones or calcifications are indistinct after iodine subtraction.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports on virtual unenhanced imaging have been optimistic [25]. The biggest drawback of virtual unenhanced imaging is that small calculi might be missed [26]. Even small calculi can be important in patients with hematuria.…”
Section: Dose Saving In Ct Urographymentioning
confidence: 99%